PENGARUH SOCIAL MEDIA MARKETING DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PADA KOPI KENANGAN PANAM PEKANBARU - Yanti, Elfira Widya; Sutrisna, Endang (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the impact of Social Media Marketing and Brand Image on Purchase Decisions, both partially and simultaneously. The research employs a quantitative descriptive analysis method, with the data obtained from primary sources through the distribution of questionnaires. The collected data were then analyzed using SPSS version 27. The population in this study consists of Kopi Kenangan Panam Pekanbaru consumers, with a total sample of 99 respondents determined using the Slovin formula. The sampling technique applied was non-probability sampling, specifically accidental sampling, which selects respondents based on coincidence or availability. Data analysis using SPSS includes tests for validity, reliability, classical assumptions, as well as simple and multiple linear regression analyses. The results indicate that Social Media Marketing (X1) has a significant effect on Purchase Decisions (Y), Brand Image (X2) has a significant effect on Purchase Decisions (Y), and both Social Media Marketing (X1) and Brand Image (X2) together have a significant effect on Purchase Decisions (Y) at Kopi Kenangan Panam Pekanbaru.